Gallium oxide nanowires for UV detection with enhanced growth and material properties - Badriyah Alhalaili (Nature Portfolio, 2020)
Abstract In the last decade, interest in the use of beta gallium oxide (β-Ga2O3) as a semiconductor for high power/high temperature devices and deep-UV sensors has grown. Ga2O3 has an enormous band gap of 4.8 eV, which makes it well suited for these applications. Compared to thin films, nanowires exhibit a higher surface-to-volume ratio, increasing their sensitivity for detection of chemical substances and light. In this work, we explore a simple and inexpensive method of growing high-density gallium oxide nanowires at high temperatures. Gallium oxide nanowire growth can be achieved by heating and oxidizing pure gallium at high temperatures (~ 1000 °C) in the presence of trace amounts of oxygen. This process can be optimized to large-scale production to grow high-quality, dense and long Ga2O3 nanowires. We show the results of morphological, structural, electrical and optical characterization of the β-Ga2O3 nanowires including the optical bandgap and photoconductance. The influence of density on these Ga2O3 nanowires and their properties will be examined in order to determine the optimum configuration for the detection of UV light.